First-principle protocol for calculating ionization energies and redox potentials of solvatedmolecules and ions: theory and application to aqueous phenol and phenolate - Ghosh, Debashree; Roy, Anirban; Seidel, Robert; Winter, Bernd; Bradforth, Stephen; Krylov, Anna I. (Journal of Physical Chemistry B, 2012)
The effect of hydration on the lowest vertical ionization energy (VIE) of phenol and phenolate solvated in bulk water was characterized using the equation-of-motion ionization potential coupled-cluster (EOM-IP-CCSD) and effective fragment potential (EFP) methods (referred to as EOM/EFP) and determined experimentally by valence photoemission measurements using microjets and synchrotron radiation. The computed solvent-induced shifts in VIEs (Delta VIEs) are 0.66 and +5.72 eV for phenol and phenolate, respectively. Our best estimates of the absolute values of VIEs (7.9 and 7.7 eV for phenol and phenolate) agree reasonably well with the respective experimental values (7.8 +/- 0.1 and 7.1 +/- 0.1 eV). The EOM/EFP scheme was benchmarked against full EOM-IP-CCSD using microsolvated phenol and phenolate clusters. A protocol for calculating redox potentials with EOM/EFP was developed based on linear response approximation (LRA) of free energy determination. The oxidation potentials of phenol and phenolate calculated using LRA and EOM/EFP are 1.32 and 0.89 V, respectively; they agree well with experimental values.